Strategi Peningkatan Kinerja Balai Benih Ikan Dinas Kelautan dan Perikanan Kabupaten Sukabumi - Padmoko, Sri; Marimin, -; Bintoro, M Hasjim (Institut Pertanian Bogor, 2017)
Regional Technical Implementation Unit (UPTD) of Fish Nurtury Center (BBI) Cimaja plays important role in providing high quality fish seeds and broodstock in Sukabumi as well as in supporting District Own Source Revenue (PAD). Presence and performance of UPTD BBI Cimaja are highly meaningful for enhancing production of edible freshwater fish. The aim of research is to (1) determine performance of UPTD BBI Cimaja based on Balanced Scorecard; (2) investigate factors affecting performance of UPTD BBI Cimaja based on Balanced Scorecard; and (3) develop strategy for improving performance of UPTD BBI Cimaja based on Balanced Scorecard. The performance was determined based on balanced scorecard using AHP software, while the strategy development for improving main task and function of BBI Cimaja was processed using SWOT and AHP. Based on balanced scorecard perspective, the maximum performance of UPTD BBI Cimaja has not been reached, thus the improvement through intensive and aggressive strategy of growth and development is required. The results showed 23 factors influencing performance of UPTD BBI Cimaja, consisting of 2 financial factors, 10 customer factors, 6 internal factors, and 5 learning and growth factors. Based on AHP and SWOT analysis, the concrete strategy for performance enhancement regarding to customer perspective was translocation that provides sufficient water sources, and new fish pond construction supported by Regional Government Budget (APBD) to maintain BBI reputation, as well as increase in seed diversity and production to improve number of customers.